On the production economics of cattle - Mundlak, Yair; Huang, He; Favaro, Edgardo (International Food Policy Research Institute, 1995)
Two empirical regularities in the beef-cattle sector have been observed for a long time. First, the time-series for cattle stock exhibits strong cyclicity with a period of several years. Second, beef supply seesms to be negatively related to price. The authors attempt to gain insight into the issue of technology's role in the the dynamics of this sector. They analyze data for three countries with different technologies: Argentina, Uruguay and the United States.